Propositions méthodologiques pour l’amélioration automatique des contrastes de couleur - application aux cartes de risque - Elisabeth Chesneau (Unité Mixte de Recherche 8504 Géographie-cités, 2006)
Maps could have a lot of surimposed informations, as risk maps. Thus, data are difficult to portray. We believe a best use of colour could improve their legibility. Therefore, we propose a model to automatically improve colour contrasts in these maps. Our model is based on Itten colour contrasts theory, a Swiss painter of the Bauhaus of the twentieth century.